Proposal of the next incarnation of accelerator test facility at KEK for the international linear collider - Araki, S; Hayano, H; Higashi, Y; Honda, Y; Kanazawa, K; Kubo, K; Kume, T; Kuriki, M; Kuroda, S; Masuzawa, M; Naito, T; Sugahara, O; et al. (2005)
To reach design luminosity, the International Linear Collider (ILC) must be able to create and reliably maintain nanometer size beams. The ATF damping ring is the unique facility where ILC emittances are possible. In this paper we present and evaluate the proposal to create a final focus facility at the ATF which, using compact final focus optics and an ILC-like bunch train, would be capable of achieving 37 nm beam size. Such a facility would enable the development of beam diagnostics and tuning methods, as well as the training of young accelerator physicists.